Teaching New Immigrants in Estonian Schools – Challenges for a Support Network - Trasberg, Karmen; Kond, Juta (Acta Paedagogica Vilnensia, 2017)
Modern school administration is more and more focused on teamwork and it is of utmost importance to find suitable cooperation formats along with different networks to support the education and adaptation of the new immigrants. The main goal of this research paper is to describe and analyze the experiences, opinions and expectations of school administration and support specialists about the ways of teaching and supporting the newly arrived immigrant pupils (refugees, asylum seekers and other immigrant children who lived in Estonia for less than five years). In the empirical part of the research, data is collected with semistructured interviews from the administrative or support team members of 12 Estonian schools which have had experiences with teaching new immigrants. Qualitative inductive content analysis is used as the method of data analysis. The results of the research show that the attitudes of the recipient school societies are rather positive. Language learning is set as a priority due to its being the main avenue for supporting integration and involvement. The shortage of adapted textbooks, lack of support specialists and limited resources to motivate teachers and compensate the extra work were brought out as the main bottlenecks in involving new immigrants.
Keywords: new immigrants; adaptation; teaching of refugees; support networks